A new species of Hyalella (Crustacea: Amphipoda: Hyalellidae) from Itatiaia National Park, Brazil: an epigean freshwater amphipod with troglobiotic traits at 2,200 meters of altitude - Rodrigues, Stella Gomes; Senna, André R.; Quadra, Adriana; Bueno, Alessandra Angélica De Pádua (Zootaxa, 2017)
A new species of the freshwater amphipod Hyalella Smith, 1874 is described for the plateau of the Itatiaia National Park, located between the states of Minas Gerais and Rio de Janeiro, southeastern Brazil. This is the first Brazilian species of Hyalella found at more than 2,200 meters of altitude. The specimens were found in a small stream, buried under rocks, in the higher area of the Park. The main morphological characteristics that differentiate the new species are the extreme reduction of the size of the uropod 3, absence of apical setae on telson, absence of comb-scales on gnatopods 1 and 2, absence of curved seta on inner ramus of uropod 1 and sternal gills tubular on pereonites 3 to 7. The new species presents similarities with some cave species of the genus, apparently being troglophile and that is the process of adaptation to the hypogean habitat. The importance of creating new protected areas for the conservation of Hyalella in Brazil is discussed.